2017
DOI: 10.1002/ajmg.a.38542
|View full text |Cite
|
Sign up to set email alerts
|

Marked yield of re‐evaluating phenotype and exome/target sequencing data in 33 individuals with intellectual disabilities

Abstract: The diagnosis of intellectual disability/developmental delay (ID/DD) benefits from the clinical application of target/exome sequencing. The yield in Mendelian diseases varies from 25% to 68%. The aim of the present study was to identify the genetic causes of 33 ID/DD patients using target/exome sequencing. Recent studies have demonstrated that reanalyzing undiagnosed exomes could yield additional diagnosis. Therefore, in addition to the normal data analysis, in this study, re-evaluation was performed prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
(33 reference statements)
0
30
0
Order By: Relevance
“…Several ES studies have focused on individuals with varying presentations of NDDs and have identified genetic causes in as many as 61% of cases. 1,11,12…”
Section: Introductionmentioning
confidence: 99%
“…Several ES studies have focused on individuals with varying presentations of NDDs and have identified genetic causes in as many as 61% of cases. 1,11,12…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing studies that report the diagnostic yield (ie, percentage of pathogenic variant carriers identified in a cohort) in NDDs are few but are becoming increasingly common. Estimates of diagnostic yield vary considerably across individual studies (8% 5 –61% 6 ). This likely reflects differences in measurement, reporting, and clinical characteristics such as etiology and disorder type/subtype.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the probability of finding a diagnosis strongly depends on the diagnostic techniques that are available. The diagnostic yield has increased dramatically in the last few years (current range: 25%–68%) since NGS technologies were developed (Cherot et al, ; Deciphering Developmental Disorders Study, ; Evers et al, ; Vissers et al, ; Xiao et al, ). Therefore, it is important to explain to families that even in cases where a genetic cause of intellectual disability is strongly suspected, an aetiological clarification is not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic yield has increased dramatically in the last few years (current range: 25%-68%) since NGS technologies were developed (Cherot et al, 2017;Deciphering Developmental Disorders Study, 2017;Evers et al, 2017;Vissers et al, 2017;Xiao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%